2011
DOI: 10.1097/adm.0b013e3181ee77cl
|View full text |Cite
|
Sign up to set email alerts
|

Group-Based Strategies for Stress Reduction in Methadone Maintenance Treatment

Abstract: Objectives To assess methadone maintenance treatment (MMT) patients’ willingness to use, and perceived efficacy of, conventional and unconventional group stress reduction treatments Methods A survey, developed by the authors, was administered to 150 MMT patients. Results Levels of treatment willingness and perceived efficacy for both conventional and unconventional treatments were relatively high; however, ratings for conventional interventions were, on average, significantly higher than those for unconven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Most studies have found no differences in length of time in treatment between genders (Kelly et al, 2011;Peles et al, 2008), and others found that females were more likely than males to be retained in treatment N 1 year (Deck & Carlson, 2005;Hser, Anglin, & Liu, 1990). Interpretations for why females may remain in treatment longer than males include extra motivation to abstain from drug use to retain custody of children, and the finding that females tend to utilize support services such as group and individual therapy sessions more frequently than males (Barry et al, 2011;Schiff, Levit, & Moreno, 2007). Chronically heroin-dependent females (vs. males) have also been found to have poorer overall health status, more dysfunctional families of origin, and greater mental health problems (Chatham, Hiller, Rowan-Szal, Joe, & Simpson, 1999;Grella & Lovinger, 2012), perhaps motivating them to remain in care and use more treatment services.…”
Section: Introductionmentioning
confidence: 90%
“…Most studies have found no differences in length of time in treatment between genders (Kelly et al, 2011;Peles et al, 2008), and others found that females were more likely than males to be retained in treatment N 1 year (Deck & Carlson, 2005;Hser, Anglin, & Liu, 1990). Interpretations for why females may remain in treatment longer than males include extra motivation to abstain from drug use to retain custody of children, and the finding that females tend to utilize support services such as group and individual therapy sessions more frequently than males (Barry et al, 2011;Schiff, Levit, & Moreno, 2007). Chronically heroin-dependent females (vs. males) have also been found to have poorer overall health status, more dysfunctional families of origin, and greater mental health problems (Chatham, Hiller, Rowan-Szal, Joe, & Simpson, 1999;Grella & Lovinger, 2012), perhaps motivating them to remain in care and use more treatment services.…”
Section: Introductionmentioning
confidence: 90%
“…To improve the current situation of limited psychological service resources in China, to equip methadone treatment centers with professional psychotherapists and to provide psychological intervention services for MMT patients are all indispensable. This is also advocated by relevant research [32,34].…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, improving the current situation of limited psychological service resources in China and providing psychological intervention services (including psychological counseling, psychotherapy, social-family support) for MMT patients are conducive to reducing the risk of anxiety disorder. This is also advocated by relevant research 34,41 .…”
Section: Discussionmentioning
confidence: 87%